Cholesterol metabolism regulation mediated by SREBP-2, LXRα and miR-33a in rainbow trout (Oncorhynchus mykiss) both in vivo and in vitro - Zhu, Tengfei (PLoS One, 2020)
Cholesterol metabolism is greatly affected in fish fed plant-based diet. The regulation of cholesterol metabolism is mediated by both transcriptional factors such as sterol regulatory element-binding proteins (SREBPs) and liver X receptors (LXRs), and posttranscriptional factors including miRNAs. In mammals, SREBP-2 and LXRα are involved in the transcriptional regulation of cholesterol synthesis and elimination, respectively. In mammals, miR-33a is reported to directly target genes involved in cholesterol catabolism. The present study aims to investigate the regulation of cholesterol metabolism by SREBP-2 and LXRα and miR-33a in rainbow trout using in vivo and in vitro approaches. In vivo, juvenile rainbow trout of ~72 g initial body weight were fed a total plant-based diet (V) or a marine diet (M) containing fishmeal and fish oil. In vitro, primary cell culture hepatocytes were stimulated by graded concentrations of 25-hydroxycholesterol (25-HC). The hepatic expression of cholesterol synthetic genes, srebp-2 and miR-33a as well as miR-33a level in plasma were increased in fish fed the plant-based diet, reversely, their expression in hepatocytes were inhibited with the increasing 25-HC in vitro. However, lxrα was not affected neither in vivo nor in vitro. Our results suggest that SREBP-2 and miR-33a synergistically enhance the expression of cholesterol synthetic genes but do not support the involvement of LXRα in the regulation of cholesterol elimination. As plasma level of miR-33a appears as potential indicator of cholesterol synthetic capacities, this study also highlights circulating miRNAs as promising noninvasive biomarker in aquaculture.